Effectiveness of common water-reducing admixtures in alkali-activated slag pastes with different types of activator - Bílek, Vlastimil; Hrubá, Valeriia; Hrubý, Petr; Kalina, Lukáš (IOP Publishing, 2021)
Rheology of alkali-activated slag (AAS) is a very complex issue, where the activator nature as well as its dose play an important role. Moreover, the use of water-reducing admixtures in these systems is an issue, as they often do not work properly. This could be attributed to the high pH as well as to the surface chemistry of AAS. Therefore, lignosulfonate-, polynaphthalene- and polycarboxylate-based superplasticizers were used to modify AAS pastes with sodium waterglass, hydroxide and carbonate activator. These pastes were tested using a rotational rheometer in an oscillatory shear mode of increasing shear strain to observe the evolution of viscoelastic moduli and to determine the oscillatory stress corresponding to the linear viscoelastic region limit ("yield point") and to the crossover point, where the storage modulus equals the loss modulus ("flow point"). In most cases, the used plasticizers did not improve the rheological properties; the only exception was the lignosulfonate one in sodium hydroxide-activated slag.

Rheology of alkali-activated slag (AAS) is a very complex issue, where the activator nature as well as its dose play an important role. Moreover, the use of water-reducing admixtures in these systems is an issue, as they often do not work properly. This could be attributed to the high pH as well as to the surface chemistry of AAS. Therefore, lignosulfonate-, polynaphthalene- and polycarboxylate-based superplasticizers were used to modify AAS pastes with sodium waterglass, hydroxide and carbonate activator. These pastes were tested using a rotational rheometer in an oscillatory shear mode of increasing shear strain to observe the evolution of viscoelastic moduli and to determine the oscillatory stress corresponding to the linear viscoelastic region limit ("yield point") and to the crossover point, where the storage modulus equals the loss modulus ("flow point"). In most cases, the used plasticizers did not improve the rheological properties; the only exception was the lignosulfonate one in sodium hydroxide-activated slag.
Effectiveness of common water-reducing admixtures in alkali-activated slag pastes with different types of activator
Keywords: alkali-activated slag; rheology; plasticizer; amplitude sweep; activator; alkali-activated slag; rheology; plasticizer; amplitude sweep; activator